Faktor yang Mempengaruhi Keterampilan Fisik Motorik pada Anak Usia Dini Melalui Pembelajaran Berbasis Proyek di Sekolah - Amelia Alfiaty; Agustina Ngabito; Salsabilla Tri Febrianti; Nena Pratiwi Bone; Putri M. Halim (Prodi Sastra Jepang Universitas Ngudi Waluyo, 2024)
The development of physical motor skills in early childhood is an important foundation that supports learning readiness, optimal growth, and the ability to adapt to the environment. This study aims to identify and analyze factors that influence the development of motor skills in early childhood through the implementation of project-based learning (PBL) in the school environment. Furthermore, this study evaluates the effectiveness of the PBL approach in improving gross and fine motor skills. The study method is based on a descriptive analysis of the implementation of projects designed by considering the relevance of activities, the level of challenge, and suitability to children's developmental abilities. The results show that project-based learning is proven to strengthen children's motor skills, especially when project activities involve physical exploration, problem solving, and the use of concrete media. Competent teacher support in designing and facilitating PBL activities is a key factor in the program's success. In addition, the availability of diverse and safe learning materials contributes significantly to sustainable motor stimulation. Overall, the PBL approach is considered effective in supporting the physical motor development of early childhood and can be adopted as an innovative, child-centered learning strategy.